2020
DOI: 10.1007/s12325-020-01444-5
|View full text |Cite
|
Sign up to set email alerts
|

Asthma-Related Health Outcomes Associated with Short-Acting β2-Agonist Inhaler Use: An Observational UK Study as Part of the SABINA Global Program

Abstract: Introduction: Patients with asthma typically increase short-acting b 2-agonists (SABA) use with worsening symptoms. Excessive SABA use may lead to a higher risk of adverse outcomes. We evaluated, in a large population cohort, an association between SABA inhaler use and asthma exacerbations and healthcare utilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
133
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 82 publications
(150 citation statements)
references
References 39 publications
13
133
0
4
Order By: Relevance
“…The results from the multivariate model run on the IQVIA LPD cohort showed that patients who had more than two SABA canisters/year have a 30% higher likelihood of experiencing exacerbations when compared to patients who had no more than two SABA canisters/year. The latter result is in total agreement with results from SABINA I study performed in the UK [15], which found a 20% increased risk of exacerbations for both step 1-2 and 3-5 patients who had a high level of SABA use (i.e., more than two canisters/year) [15]. Furthermore, GINA guidelines state that dispensing more than two SABA canisters/year is associated with an increased risk of emergency department visit or hospitalization independent of severity [1].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The results from the multivariate model run on the IQVIA LPD cohort showed that patients who had more than two SABA canisters/year have a 30% higher likelihood of experiencing exacerbations when compared to patients who had no more than two SABA canisters/year. The latter result is in total agreement with results from SABINA I study performed in the UK [15], which found a 20% increased risk of exacerbations for both step 1-2 and 3-5 patients who had a high level of SABA use (i.e., more than two canisters/year) [15]. Furthermore, GINA guidelines state that dispensing more than two SABA canisters/year is associated with an increased risk of emergency department visit or hospitalization independent of severity [1].…”
Section: Discussionsupporting
confidence: 92%
“…Secondly, exacerbations are not directly recorded in the database, thus requiring us to use an algorithm to detect their occurrence. However, our results, showing a higher risk of exacerbations for patients with more than two SABA canisters/year, are in line with the literature [ 4 7 , 15 ], indicating the appropriateness of the rules set to detect exacerbations. Moreover, as observed previously [ 15 , 25 27 ], the likelihood of experiencing exacerbations was increased with number of comorbidities, older age, and female sex.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our findings that high SABA users experienced more moderate and severe asthma exacerbations and also more often had a history of courses of antibiotics and oral steroids, are in line with findings in other studies. 6,8,[19][20][21][22][23][24] This could imply that SABA usage in the preceding week can be extrapolated to SABA use in the previous year. Hence, this shows that a clinically easy and quick way of assessing SABA use, ie by merely asking the patient about their SABA use in the preceding week, could be an indicator for the risk of future exacerbations.…”
Section: Association Of High Saba Use With Exacerbationsmentioning
confidence: 99%